The Genetics and Epigenetics of Ventricular Arrhythmias in Patients Without Structural Heart Disease - Wang, Mengru; Tu, Xin (Frontiers in Cardiovascular Medicine, 2022)
Ventricular arrhythmia without structural heart disease is an arrhythmic disorder that occurs in structurally normal heart and no transient or reversible arrhythmia factors, such as electrolyte disorders and myocardial ischemia. Ventricular arrhythmias without structural heart disease can be induced by multiple factors, including genetics and environment, which involve different genetic and epigenetic regulation. Familial genetic analysis reveals that cardiac ion-channel disorder and dysfunctional calcium handling are two major causes of this type of heart disease. Genome-wide association studies have identified some genetic susceptibility loci associated with ventricular tachycardia and ventricular fibrillation, yet relatively few loci associated with no structural heart disease. The effects of epigenetics on the ventricular arrhythmias susceptibility genes, involving non-coding RNAs, DNA methylation and other regulatory mechanisms, are gradually being revealed. This article aims to review the knowledge of ventricular arrhythmia without structural heart disease in genetics, and summarizes the current state of epigenetic regulation.